Vprašalnice Etnološkega atlasa in Slovenci - Đaković, Branko (Etnolog. Nova vrsta (Ljubljana), 2003)
The article presents and analyses the data which were collected, using, ethnological questionnaires, in the territory of Slovenia until approximately the 1970s. The questionnaire were part of the preparations for producing an ethnological atlas of Yugoslavia. The collected material is from 251 Slovene villages and covers 157 themes. It is comparable with the material collected in about 3100 villages in the territory of the former Yugoslavia.
Keywords: ethnology; etnologija; etnološki altasi; vprašalnice; raziskovalno delo; gradivo; Slovenia; Slovenija